2016
DOI: 10.1017/s1368980015003651
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of iron status and Hb in the Bangladesh population: the role of groundwater iron

Abstract: Objective: Using data from the national micronutrients survey 2011-2012, the present study explored the determinants of Fe status and Hb levels in Bangladesh with a particular focus on groundwater Fe. Design: Cross-sectional study conducted at the nationwide scale. Settings: The survey was conducted in 150 clusters, fifty in each of the three strata of rural, urban and slum. Subjects: Three population groups: pre-school age children (6-59 months; PSAC), school age children (6-14 years; SAC) and non-pregnant no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
79
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(87 citation statements)
references
References 31 publications
7
79
1
Order By: Relevance
“…A recent study has revealed that the higher prevalence of anemia in Bangladesh is not associated with iron deficiency [10]. The nationwide prevalence of anemia (33.1% in children under five years of age and 26% in women) was more than three times higher than that of iron deficiency in children (10.7%) and women (7.1%), suggesting other determining factors for this unexpected scenario [10]. In this context, the role of congenital Hb disorders along with micronutrient (such as dietary iron, vitamin A, folate and Zn) deficiency could explain this phenomenon [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has revealed that the higher prevalence of anemia in Bangladesh is not associated with iron deficiency [10]. The nationwide prevalence of anemia (33.1% in children under five years of age and 26% in women) was more than three times higher than that of iron deficiency in children (10.7%) and women (7.1%), suggesting other determining factors for this unexpected scenario [10]. In this context, the role of congenital Hb disorders along with micronutrient (such as dietary iron, vitamin A, folate and Zn) deficiency could explain this phenomenon [10].…”
Section: Introductionmentioning
confidence: 99%
“…The nationwide prevalence of anemia (33.1% in children under five years of age and 26% in women) was more than three times higher than that of iron deficiency in children (10.7%) and women (7.1%), suggesting other determining factors for this unexpected scenario [10]. In this context, the role of congenital Hb disorders along with micronutrient (such as dietary iron, vitamin A, folate and Zn) deficiency could explain this phenomenon [10]. A recent study has indicated that about 28% of assessed rural women have beta thalassemia or HbE [11].…”
Section: Introductionmentioning
confidence: 99%
“…High levels of iron in groundwater result in unpleasant esthetic experiences with water, e.g., bad taste, odor, and color. However, recent studies in Bangladesh have revealed that iron in groundwater is a good source of absorbable iron in humans, leading to good iron and hemoglobin status in the population (Merrill 2011;Rahman 2016). Based on these findings, policymakers have endorsed the importance of considering groundwater iron in anemia/micronutrient deficiency control programs (Institute of Public Health Nutrition and United Nation Children's Fund 2016).…”
Section: Background and Rationalementioning
confidence: 99%
“…It is worth noting that the prevalence of anaemia was also reported in the BDHS survey from 2011, and results were much higher than those reported in the icddr,b survey of 2012 (for example, 40.0% compared to 26.0% among NPNL women). This may be explained by slight differences in analytical methods (Rahman et al, 2016b). The icddr,b survey used venous blood samples, whereas the BDHS survey used capillary blood samples .…”
Section: Micronutrients Of Public Health Significancementioning
confidence: 99%
“…The icddr,b survey used venous blood samples, whereas the BDHS survey used capillary blood samples . Interestingly, the prevalence of iron deficiency and iron deficiency anaemia was found to be relatively low, despite the high prevalence of inadequate dietary iron intakes and the relatively high prevalence of anaemia (Rahman et al, 2016b). This has been attributed to the presence of highly bioavailable iron in groundwater in many regions of Bangladesh (Merrill et al, 2012;Rahman et al, 2016b).…”
Section: Micronutrients Of Public Health Significancementioning
confidence: 99%